2019
DOI: 10.1093/cid/ciz959
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Enrollment by Sex in Human Immunodeficiency Virus Clinical Trials in the United States

Abstract: Background Women are underrepresented in human immunodeficiency virus (HIV) research in the United States. To determine if women screening for HIV clinical trials enrolled at lower rates than men, we performed a retrospective, cross-trial analysis. Methods We conducted an analysis of screening and enrollment during 2003–2013 to 31 clinical trials at 99 AIDS Clinical Trials Group network research sites in the United States. Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Sex differences are also one of the factors that affect the success of screening (20,21). The results showed that sex was significantly correlated with screening failure.…”
Section: Influencing Factors Of Screening Failurementioning
confidence: 98%
“…Sex differences are also one of the factors that affect the success of screening (20,21). The results showed that sex was significantly correlated with screening failure.…”
Section: Influencing Factors Of Screening Failurementioning
confidence: 98%
“…D espite bearing a significant burden of the HIV epidemic, 1,2 women remain chronically underrepresented in HIV research. 3,4 In a landscape analysis of HIV cure-related research, women accounted for 17.3% of participants in human trials conducted through 2017. 5 A systematic review of 104 HIV cure-related studies published between 1995 and 2012 showed that women represented a median of 11.1% participants in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses from the ACTG indicate that the paucity of women in studies is not due to a higher rate of screening out (at least in the USA), 17 highlighting the importance of advocacy, education, support and outreach to facilitate increased screening for studies. The NIH policy on considering SABV (sex as a biological variable) in all vertebrate animal and human studies, which was instituted relatively recently, also has the potential to enhance this critical area of HIV cure research.…”
Section: Discussionmentioning
confidence: 99%